Impact of automobile waste on heavy metal accumulation and microbial activity at two selected Auto-Mechanic Workshops in Kumasi, (Ashanti Region) - Ghana - Benefo, Samuel Kwasi (University of Cape Coast, 2020)
Auto mechanics have over the years played a major role in the transport industry in Ghana by providing services to many road users including; heavy duty cars, tankers, salon cars, commercial vehicle among others. In the process of discharging their duties, they intentionally and unintentionally deposit various waste from vehicles on the soil within the workshops and the adjoining fields. A survey was conducted to assess the impact of automobile waste on soil heavy metal levels and soil microbial activity. Two auto mechanic workshops at Edwenase and South Suntreso in Kumasi Metropolis (Ashanti Region of Ghana) were considered. The experimental design used was Randomized Complete Block Design. Composite soil samples were taken at depths of 0-10 cm and 10-30 cm from the upper part through to the middle part and to the valley bottom and analyse for heavy metals including; Pb, As, Zn and Cd. Selected parts of maize and plantain at the adjoining fields were also randomly sampled for heavy metal accumulation analysis. Soil samples were subjected to microbial activity analysis using the basal respiration method. The levels of Zinc recorded in the soil sample were highly above the FAO acceptable limit of 3.5 – 6 mg/kg. The levels of arsenic at South Suntreso were within the FAO acceptable limit of 20 mg kg-1. Pb of plant samples had 0.03 mg/kg level. Zinc levels emerged the highest at 15.47 mg/kg in plant biomass. At South Suntreso, the valley bottom recorded the highest microbial activity of 65.24 mgCO2/kg soil/day. After the study, it was established that there were some traces of heavy metals in soil and plant samples at the two study sites; and the presence of the heavy metals had an effect on soil microbial activities.
xii,121p:, ill
Keywords: Auto mechanic workshop; Heavy metal uptake; Microbial activity; Significant difference; Soil pollution; Soil samples